Implementation of Intrinsic Factors of Human Resource Performance in Palembang Water Tourism - Zaleha Trihandayani; Ahmad Dzaky Fawwaz (International Journal of Management Science and Information Technology, 2024)
The research with the aim was conducted determining the implementation of intrinsic factors of human resource performance in Palembang water tourism. Employee research with associative the type. The sample in this research was 200 Palembang water employee for tourism employees who were selected using the proportional random sampling method. Used in the data of research is primary data a questionnaire data with collection method. Also used is Structural analysis modeling equation (SEM) The technique data analysis with an Application Program. The results and conclusions research show that: (1) positive and significant there is the application of intrinsic discipline factors on people performance. (2) There is the application positive and significant for influence organizational many culture factors on employee attitude. (3) There is a positive and significant influence of competency implementation on employee performance. (4) There is a negative and insignificant effect of the application of intrinsic environmental factors on employee performance. (5) A positive result and significant when the application of intrinsic motivation factors on employee performance. (6) Motivation strengthens discipline towards employee performance. (7) Motivation strengthens organizational culture on the performance of human resources in Palembang water tourism. The findings from this research are that increasing or decreasing has no effect organizational culture performance on employee.